Analysis of the Implementation of the XYZ Core Banking System at PT BPR Hariarta Sedana - Pandhu, I Made Suri (Politeknik Ganesha Medan, 2024)
: The Core Banking System (CBS) is often referred to as the heart of a bank due to its crucial role in banking activities. Core Banking is used for processing loans, savings, customer information storage, and various other services. Real-time interaction is required to process banking activities. Each bank has its own strengths, needs, and target market in order to conduct its business. These needs must be supported by reliable, flexible information technology solutions that are ready for further development according to the bank's requirements. The transformation of Bank Perekonomian Rakyat (BPR) is a critical step in supporting economic growth for both the bank and its customers. This study highlights the latest trends in the banking industry related to banking digitalization, such as real-time online integration with delivery channels, including mobile banking services. This analysis also identifies the weaknesses of the previous banking system and the strengths relevant to the transformation desired by BPR's business needs. The availability of technology, system integration, and IT architecture are the focus to understand the existing infrastructure. For now, the implemented changes have significantly impacted the speed of operational performance and services, as well as better control of employee working hours.